Identifying post-marital residence patterns in prehistory: A phylogenetic comparative analysis of dwelling size - Hrnčíř, Václav; Duda, Pavel; Šaffa, Gabriel; Květina, Petr; Zrzavý, Jan (PloS one, 2020)
Post-marital residence patterns are an important aspect of human social organization. However, identifying such patterns in prehistoric societies is challenging since they leave almost no direct traces in archaeological records. Cross-cultural researchers have attempted to identify correlates of post-marital residence through the statistical analysis of ethnographic data. Several studies have demonstrated that, in agricultural societies, large dwellings (over ca. 65 m2) are associated with matrilocality (spouse resides with or near the wife's family), whereas smaller dwellings are associated with patrilocality (spouse resides with or near the husband's family). In the present study, we tested the association between post-marital residence and dwelling size (average house floor area) using phylogenetic comparative methods and a global sample of 86 pre-industrial societies, 22 of which were matrilocal. Our analysis included the presence of agriculture, sedentism, and durability of house construction material as additional explanatory variables. The results confirm a strong association between matrilocality and dwelling size, although very large dwellings (over ca. 200 m2) were found to be associated with all types of post-marital residence. The best model combined dwelling size, post-marital residence pattern, and sedentism, the latter being the single best predictor of house size. The effect of agriculture on dwelling size becomes insignificant once the fixity of settlement is taken into account. Our results indicate that post-marital residence and house size evolve in a correlated fashion, namely that matrilocality is a predictable response to an increase in dwelling size. As such, we suggest that reliable inferences about the social organization of prehistoric societies can be made from archaeological records.
Keywords: Demography; manželství; Family Characteristics; Humans; Phylogeny; Population Dynamics; archeologie; Female; Housing; Residence Characteristics; Anthropology; lidé; dějiny starověku; populační dynamika; bydlení; charakteristiky bydlení; Marriage; ženské pohlaví; Male; fylogeneze; History, Ancient; Archaeology; charakteristiky rodiny; antropologie; demografie; mužské pohlaví